MENINGKATKAN AKUNTABILITAS PENGELOLAAN DANA DESA MELALUI KOMPETENSI PERANGKAT DESA, SISTEM PENGENDALIAN INTERNAL DAN PARTISIPASI MASYARAKAT : IMPROVING VILLAGE FUND MANAGEMENT ACCOUNTABILITY THROUGH THE COMPETENCE OF VILLAGE EQUIPMENT, INTERNAL CONTROL SYSTEM AND COMMUNITY PARTICIPATION - Ayem, Sri; Ariyanti, Nurul (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
This study aims to examine and analyze the factors that influence the accountability of managing village funds. The population in this study was village officials in Kapanewon Sewon and Kapanewon Imogiri. The research sample was taken using a purposive sampling method based on Permendagri Number 20 of 2018. Data collection was carried out using a questionnaire and a sample of 96 village officials was obtained. The analysis used was multiple regression analysis using IBM SPSS version 26. The results showed that village apparatus competence had no effect on village fund management accountability, internal control systems and community participation had a positive effect on village fund management accountability. While simultaneously showing the competence of village officials, internal control systems and community participation have a positive effect on village fund management accountability. The implication of this research is that accountability for managing village funds can be realized by improving the internal control system and community participation through monitoring and evaluation as well as dissemination of village funds to the community.